2011
DOI: 10.20460/jgsm.2011515802
|View full text |Cite
|
Sign up to set email alerts
|

Store Brand Purchase Intention: Effects of Risk, Quality, Familiarity and Store Brand Shelf Space

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
2
25
0
4
Order By: Relevance
“…Thus, store brand awareness, which is related to brand familiarity, recognition and recall, plays the most important role in enhancing consumers' purchase intention (Dursun et al 2011). These results are in line with Jara and Cliquet (2012), stressing that brand awareness positively and directly influences consumers' response, being the main component in the creation of store Brand Equity.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, store brand awareness, which is related to brand familiarity, recognition and recall, plays the most important role in enhancing consumers' purchase intention (Dursun et al 2011). These results are in line with Jara and Cliquet (2012), stressing that brand awareness positively and directly influences consumers' response, being the main component in the creation of store Brand Equity.…”
Section: Discussionsupporting
confidence: 81%
“…Retailers always place their store brands in shelves adjacent to national brands. Dursun et al (2011) found that shelf space allocation contributes significantly in enhancing product familiarity and perceived quality. Zameer et al (2012) stated that private labels are placed near to national brands to make consumer perceive that they are high quality products.…”
Section: Shelf Space Allocationmentioning
confidence: 99%
“…Store brands also known as private label brands, and own brands have drawn great academic and managerial attention in parallel with their rapidly growing market share [Dursun et al 2011]. Store brands are owned, managed and marketed by a particular retailer, being present in numerous retailing formats and product categories [Sprott and Shimp 2004].…”
Section: Scientific Problemmentioning
confidence: 99%